2022
DOI: 10.2991/assehr.k.220105.036
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of New Media Influencing People’s Attitude and Cognition to GMF

Abstract: Nowadays, new media plays an important role in people's life. The idea of media attention proved that media would influence the audiences' attitude, opinion direction, opinion strength, actual behavior, and cognitive learning. In this review, the readers' attitude and cognition will be fully analyzed in a controversial topic---genetically modified food (GMF). By reading substantial relevant literature reviews and researches, the result is that new media certainly changed the readers' attitude and cognition, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Wibowo and Karlinah [7] (2018) also revealed that new media (e.g., Twitter) could set the social media agenda to influence traditional media. Today, social media has a considerable influence on people's lives, even affecting politicians [8] and their attitudes on some pertinent social issues [9] . Typically, the public is already informed via social media about a piece of news before it is formally covered by the official news media.…”
Section: Research On the Impact Of New Mediamentioning
confidence: 99%
“…Wibowo and Karlinah [7] (2018) also revealed that new media (e.g., Twitter) could set the social media agenda to influence traditional media. Today, social media has a considerable influence on people's lives, even affecting politicians [8] and their attitudes on some pertinent social issues [9] . Typically, the public is already informed via social media about a piece of news before it is formally covered by the official news media.…”
Section: Research On the Impact Of New Mediamentioning
confidence: 99%